2015
DOI: 10.1007/s00421-015-3316-4
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of whole body vibration on patellar tendon properties and knee extension torque

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Rieder, F., Wiesinger, H.-P., Kösters, A., Müller, E., Seynnes, O. R.Immediate effects of whole body vibration on patellar tendon properties and knee extension torque. AbstractPurpose: Reports about the immediate effects of whole body vibration (WBV) exposure upon torque production capacity are inconsistent. However, the changes in the torque-angle relationship observed by some authors after WBV may hinder the measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(54 reference statements)
3
7
0
Order By: Relevance
“…Another study, however, revealed no effect on patellar tendon stiffness after eight weeks of WBV training [12]. Regarding the acute effects of WBV on tendon properties, Rieder et al reported that a single bout of WBV did not change patellar tendon stiffness [13]. In our study, we found no significant changes in the patellar and quadriceps tendon stiffness of both hemiparetic and unaffected limbs immediately after WBV exercise, which was consistent with previous studies [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another study, however, revealed no effect on patellar tendon stiffness after eight weeks of WBV training [12]. Regarding the acute effects of WBV on tendon properties, Rieder et al reported that a single bout of WBV did not change patellar tendon stiffness [13]. In our study, we found no significant changes in the patellar and quadriceps tendon stiffness of both hemiparetic and unaffected limbs immediately after WBV exercise, which was consistent with previous studies [13].…”
Section: Discussionsupporting
confidence: 91%
“…Whole body vibration (WBV) has been applied to improve muscles strength, power, and flexibility [8]. However, there have been limited reports regarding the effect of vibration on tendon stiffness, with inconsistent results [9][10][11][12][13]. Shear wave elastography is a commonly used tool in the evaluation of the musculoskeletal system, and it considered to be a reliable method for the assessment of patellar and quadriceps tendon mechanical properties using shear wave velocity [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, our tallest participant was only 177 cm and the two reference points (the patella and the tibial tuberosity) are less apart than the tendon’s most distal and proximal attachment sites. Therefore, the reference points for tendon tracking were clearly within the field of view in all included trials and this method is accepted as valid in the current scientific literature (Kosters et al 2014 ; Rieder et al 2016 ; Wiesinger et al 2016 ). Errors in the calculation of joint moments due to knee rotation during MVC trials could have led to inaccuracies in the tendon force calculations, which have been found to amount to up to 17 % (Arampatzis et al 2004 ; Tsaopoulos et al 2011 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, our tallest participant was only 177 cm and the two reference points (the patella and the tibial tuberosity) are less apart than the tendon’s most distal and proximal attachment sites. Therefore, the reference points for tendon tracking were clearly within the field of view in all included trials and this method is accepted as valid in the current scientific literature (Kosters et al 2014 ; Rieder et al 2016 ; Wiesinger et al 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“… 25 There is also strong evidence of the effects of WBV on fitness, including improvements in the flexibility of the lower limbs, 26 , 27 that could be justified by stretching of the muscles. 28 , 29 It was suggested that WBV would reduce the stiffness and hysteresis of the tendon, alter the properties of the intramuscular connective tissue, 29 and possibly modify those of other passive skeletal structures related to the range of motion for a determined joint 30 such as the knee. 28 Acute and short- and long-term effects of WBV exercise have been studied 21 , 28 , 29 , 31 as well as cardiovascular responses by WBV in young health adults, 32 , 33 older adults, 34 and obese women.…”
Section: Introductionmentioning
confidence: 99%